Hans Jonas, El concepto de Dios después de Auschwitz” y su relación con la idea de un pensamiento posmetafísico - Rosales Rodríguez, Amán (Pontificia Universidad Católica del Perú. Fondo Editorial, 2003)
Este trabajo ofrece una presentación y un examen crítico de una de las ideas filosófico-teológicas más controversiales y sugerentes de Hans Jonas: la de un Dios "sufriente" y "no omnipotente". Asimismo, se introducen algunas reacciones críticas a dicha noción. Posteriormente, se busca relacionarla, destacando semejanzas y diferencias, con reflexiones recientes en torno a un "pensamiento posmetafísico". Algunos comentarios sobre la actualidad o pertinencia de la propuesta jonasiana se plantean al final del trabajo.

“Hans Jonas, ‘The concept of God after Auschwitz’ and its relation to the idea of a post metaphysical though”. This essay offers a presentation and a critical examination of one of the most controversial and suggestive philosophical-theological ideas of Hans Jonas: the idea of a “suffering” and “non omnipotent” God. Furthermore a few critical reactions to that notion are introduced and briefly commented. Then, the attempt is made to connect that idea, making it explicit its resemblances and differences, with recent reflections concerning a “post metaphysical thinking”. Some remarks on the current philosophical significance of the Jonasian proposal are suggested at the end of the article.
Keywords: Filosofía; Hans Jonas; Pensamiento Posmetafísico; Teología; https://purl.org/pe-repo/ocde/ford#6.03.01